Comment on "Special segregation of Cu on the habit plane of lath-like β′ and QP2 precipitates in Al-Mg-Si-Cu alloys". (15th March 2019) - Ehlers, F.J.H.
Abstract: The recent experimental report on Cu segregation at the β′ interface in Al-Mg-Si-Cu [Y. Y. Weng et al., Scripta Mater. 151 (2018) 33] is argued to highlight either (i) a need to revisit generally accepted knowledge on the Cu stabilisation of metastable precipitates in this alloy system or (ii) an opportunity to strengthen existing theories.